Genomic architecture characterizes tumor progression paths and fate in breast cancer patients - Russnes, Hege G; Vollan, Hans Kristian Moen; Lingjærde, Ole Christian; Krasnitz, Alexander; Lundin, Pär; Naume, Bjørn; Sørlie, Therese; Borgen, Elin; Rye, Inga H; Langerød, Anita; Chin, Suet-Feung; Teschendorff, Andrew E; et al. (Science translational medicine, 2010)
Distinct molecular subtypes of breast carcinomas have been identified, but translation into clinical use has been limited. We have developed two platform-independent algorithms to explore genomic architectural distortion using array comparative genomic hybridization data to measure (i) whole-arm gains and losses [whole-arm aberration index (WAAI)] and (ii) complex rearrangements [complex arm aberration index (CAAI)]. By applying CAAI and WAAI to data from 595 breast cancer patients, we were able to separate the cases into eight subgroups with different distributions of genomic distortion. Within each subgroup data from expression analyses, sequencing and ploidy indicated that progression occurs along separate paths into more complex genotypes. Histological grade had prognostic impact only in the luminal-related groups, whereas the complexity identified by CAAI had an overall independent prognostic power. This study emphasizes the relation among structural genomic alterations, molecular subtype, and clinical behavior and shows that objective score of genomic complexity (CAAI) is an independent prognostic marker in breast cancer.